INTRA-SCHOOL DIFFICULTIES IN THE EFFECTIVENESS OF THE PROJETO CULTURA DE PAZ (PROJECT CULTURE OF PEACE) - Marina Frota Lopes; Herika Paiva Pontes; Denise Nunes Oliveira; Juliana Carneiro Melo; Jaime Emanuel Moreira Ribeiro; Mirna Albuquerque Frota (Universidade Federal do Paraná, 2019)
The present study aimed to research the intra-school difficulties for effectiveness of the culture of peace in the school. The methodological course based on the object of study was exploratory and descriptive with a qualitative approach. A case study was developed at the Municipal School of Fortaleza-Ceará, established in Regional V. The target public of the study was the management group and teachers of this public school. The data collection occurred from February to June 2015.The production of the data was carried out through semi-structured interviews. The analysis and organization of the data were performed through Content Analysis. There was communication failure, attrition and demotivation of teachers, lack of preparation for activities that contemplate peace, as well as the absence of municipal and governmental partnerships